Nuclear structure physics - Shukla, Amritanshu; Patra, Suresh Kumar (Boca Raton, FL : CRC Press, 2021)
Nuclear structure Physics connects to some of our fundamental questions about the creation of universe and its basic constituents. At the same time, precise knowledge on the subject has lead to develop many important tools of human kind such as proton therapy, radioactive dating etc. This book contains chapters on some of the crucial and trending research topics in nuclear structure, including the nuclei lying on the extremes of spin, isospin and mass. A better theoretical understanding of these topics is important beyond the confines of the nuclear structure community. Additionally, the book will showcase the applicability and success of the different nuclear effective interaction parameters near the drip line, where hints for level reordering have already been seen, and where one can test the isospin-dependence of the interaction. The book offers comprehensive coverage of the most essential topics, including: Nuclear Structure of Nuclei at or Near Drip-Lines Synthesis challenges and properties of Superheavy nuclei Nuclear Structure and Nuclear models - Ab-initio calculations, cluster models, Shell-model/DSM, RMF, Skyrme Shell Closure, Magicity and other novel features of nuclei at extremes Structure of Toroidal, Bubble Nuclei, halo and other exotic nuclei These topics are not only very interesting from theoretical nuclear physics perspective but are also quite complimentary for ongoing nuclear physics experimental program worldwide. It is hoped that the book chapters written by experienced and well known researchers/experts will be helpful for the master students, graduate students and researchers and serve as a standard & uptodate research reference book on the topics covered.
Contents Preface vii Editors ix Contributors xi 1 Magic Numbers of Cylindrical Symmetry 1 Andriana Martinou and Dennis Bonatsos 2 Skyrme and Relativistic Mean-Field Models in the Description of Symmetric, Asymmetric, and Stellar Nuclear Matter 27 O. Louren-co, M. Dutra, and P. D. Stevenson 3 Recent Parameterization in Relativistic Mean-Field Formalism 67 K.C. Naik, R.N. Panda, Bharata Kumar, and S. K. Patra 4 Nuclear Symmetry Energy in Finite Nuclei 93 M.K. Gaidarov, A.N. Antonov, D.N. Kadrev, P. Sarriguren, and E. Moya de Guerra 5 Theoretical Description of Low-Energy Nuclear Fusion 121 Raj Kumar, M. Bhuyan, D. Jain, and B. V. Carlson 6 Cluster-Decay Model for Hot and Rotating Compound Nuclei 145 BirBikram Singh and Manpreet Kaur 7 Explorations within the Preformed Cluster Decay Model 167 BirBikram Singh and Mandeep Kaur 8 Studies on Synthesis and Decay of Superheavy Elements with Z = 122 185 K. P. Santhosh and V. Safoora 9 Decay Dynamics of Ground- and Excited-State Nuclear Systems Using Collective Clusterization Approach 203 Manoj K. Sharma and Neha Grover 10 Spectroscopic Properties of Nuclei in Generalized Seniority Scheme 231 Bhoomika Maheshwari and Bijay Kumar Agrawal 11 Nuclear High-Spin Spectroscopy in the A -- 60 Mass Region 253 J. Gellanki, S.K. Mandal, and Amritanshu Shukla 12 Nuclear Structure Aspects of Bubble Nuclei 279 Akhilesh Kumar Yadav and Amritanshu Shukla 13 Correlation of Nuclear Structure Observable with the Nuclear Reaction Measurable in the Aspect of Astrophysical P-Process 295 Awanish Bajpeyi, Ajeet Singh, and Amritanshu Shukla 14 Constraining the Nuclear Matter EoS from the Properties of Celestial Objects 317 Bijay Kumar Agrawal and Tuhin Malik 15 Weak Interactions and Nuclear Structure 333 Naftali Auerbach, Vladimir Zelevinsky, and Bui Minh Loc Index 391
OCLC-licensed vendor bibliographic record.
Keywords: Nuclear structure; Nuclear physics; SCIENCE / Quantum Theory